Tree-ring Δ14C time series from 1948 to 2018 at a regional background site, China: Influences of atmospheric nuclear weapons tests and fossil fuel emissions. (1st February 2021) - Niu, Zhenchuan; Feng, Xue; Zhou, Weijian; Wang, Peng; Liu, Yu; Lu, Xuefeng; Du, Hua; Fu, Yunchong; Li, Ming; Mei, Ruochen; Li, Qiang; Cai, Qiufang
Abstract: Δ 14 C values were measured from tree-rings (1948–2018) of Pinus tabuliformis Carr. that grew at the Shangdianzi (SDZ) regional background site in China. The objectives of this study are to establish a record of atmospheric Δ 14 C, and to evaluate the influences of Chinese atmospheric nuclear tests and fossil carbon emissions on atmospheric Δ 14 C variations. The SDZ tree-ring Δ 14 C values are negative before 1956, and increase dramatically in response to global atmospheric nuclear tests, with a peak value of 844.0 ± 4.2‰ in 1964. After the Partial Test Ban Treaty in 1963, the Δ 14 C values at SDZ decrease exponentially during 1964–2018. The half-life of the Δ 14 C decrease was protracted by approximately 2.7 yr during 1964–1984, due to Chinese atmospheric nuclear tests as well as Chinese forests as a carbon source during that period. Massive fossil carbon emissions in China lead to the SDZ decrease rate that is about 1.8‰ yr −1 faster than that for the Northern Hemisphere background region during 2000–2010. SDZ Δ 14 C since 2000 show strong negative correlations with fossil carbon emissions from the Beijing-Tianjin-Hebei (BTH) region ( r 2  = 0.954) and China ( r 2  = 0.950), and a 1‰ decrease in SDZ Δ 14 C indicates an increase of 2.3 ± 0.2 Mt C and 23.3 ± 1.7 Mt C fossil carbon emissions from the BTH region and China, respectively. Graphical abstract: Image 1 Highlights: Tree ring (1948–2018) Δ 14 C values were measured at a Chinese background site. Tree ring Δ 14 C value at Shangdianzi (SDZ) shows a peak of 844.0 ± 4.2‰ in 1964. Chinese bomb test is a main factor extending 2.7 yr half-life of SDZ Δ 14 C decrease. Fossil carbon emissions in China since 2000 accelerated SDZ Δ 14 C decrease rate. Tree ring Δ 14 C at SDZ are anti-correlated with fossil carbon emissions after 2000.